PEMANFAATAN KULIT BUAH PISANG NANGKA SEBAGAI SUBSTRAT FERMENTASI PADAT PADA PRODUKSI XILANASE - dkk, Trismilah (Jurnal Rekayasa Lingkungan)
Jackfruit skin bananas (Musa sp.) one of the agricultural waste that is rich nutrients for the growth of microorganisms, can be used as a substrate of xilan for the production xilanase. The research aims to know the optimum conditionsof solid fermentation for production xilanase Bacillus licheniformis I-5 using a jackfruit skin banana as substrate. Optimization includes the incubation time for 72 hours with the interval measurement activities every six hours, the moisture content variation on the 1: 1.0 (55%); 1: 1.5 (65%); 1: 2.0 (70%); 1 : 2.5 (74%) (w / v), incubation temperature variation in the 40 °, 45 °, 50 °, 55 °, 60 ° C and the addition of carbon and nitrogen source on the concentration of 1, 2,3, 4, and 5% (w / w). Fermentation carried out in erlenmeyer 250 ml, containing 10 g cod banana jackfruit, 0.4 K2HPO4, and 0.2 MgSO4 (g / l). Results of research shows that the optimum activity xilanase to 48 hours of fermentation,moisture content 1: 1.5 (65%) and incubation temperature 50 ° C with the activity of 0410 ± 0102 U / ml. The addition of glucose and prevent xilosa activities to be 0032 ± 0007 U / ml and 0053 ± 0025 U / ml concentration in 5%. Pepton addition of 4% increased the activity is not signifi cant to control the 0487 ± 0073 U / ml.